Secular trend in height and associated factors among adolescents in Florianópolis, Santa Catarina, Brazil, between 2007 and 2017/2018 - Clair Costa Miranda; Jean Carlos Parmigiani De Marco; André de Araújo Pinto; Andreia Pelegrini (Revista Paulista de Pediatria)
ABSTRACT Objective To assess the secular trend in height among adolescents in Florianópolis between 2007 and 2017/2018, and identify factors associated with height by sex. Methods The sample included 664 adolescents from public schools in 2007 and 1,008 in 2017/2018. Height was the dependent variable, with age, economic status, sexual maturity, physical activity, body fat (skinfold thickness), and fat-free mass as independent variables. Analysis of covariance evaluated the secular trend, and multiple linear regression identified associated factors. Results There was a positive secular trend in height in both sexes when comparing the two surveys, with average increases of 3.5 cm in both sexes. Fat-free mass was a positive predictor and body fat was a negative predictor of height in both sexes. Additionally, physical activity emerged as a negative predictor of height specifically in boys. Conclusions The research revealed a positive secular trend in the height of adolescents in Florianópolis. Fat-free mass contributes positively to gains in height, whereas body fat provides a negative contribution.